TINJAUAN HUKUM INTERNASIONAL TERKAIT PENETAPAN WILAYAH KONSERVASI OLEH INGGRIS TERHADAP KEPULAUAN CAGOS YANG MASIH DALAM PERSENGKETAAN DENGAN MAURITIUS - Yanti Fristikawati; Ronaldo Lado (Dialogia Iuridica, 2021)
Every states have the rights or jurisdiction over their territory in the land and sea, and to protect their specific environment, they also have the right to purpose part of their territory as a Protected Area. Chagos archipelago is rich in the marine biodiversity which have to protect This island which place in the Indian Ocean used to be a British Colony, and in 1968 after Mauritius independence, British still exist in Chagos island based on their agreement with Mauritius to use this island for a few year, because British also have the agreement with US to use one of the island (Diego Garcia) as US Millitary Camp. In 2010 British purpose the Chagos archipelago as a protected area, which against by Mauritius, because the Cahgos Island is not British territory, its Mauritius’s territory. Based on UNCLOS 1982 only the coastal state have the rights of their marine biodiversity in their ZEE. The Convention on Biodiversity 1992, also mentioned about the rights of states to protect their biodiversity by using as protected area. IUCN as an international organization has the guidance about protected area that can be use to discuss the Chagos marine protected areas.